The effect of ammonium nitrate ratio and support types on the NPK uptake and growth of black pepper (Piper nigrum L.) in field conditions - Issukindarsyah, Issukindarsyah (Array, 2021)
The study"s objective was to determine the effect of the NO3-: NH4+ratio and types of support on NPK uptake and pepper plant growth in field conditions. The study used a completely randomized block design with three replications. The first factor was the type of support, being the deadwood and living supports in the form of Gliricidia sp. and Ceiba pentandra. The second factor was the ratio of N fertilizer forms, which were 100% NO3-, 100% NH4+, 50% NO3-:50% NH4+, 75% NO3-:25% NH4+ and 25% NO3-:75% NH4+. The results have demonstrated that the uptake of N, P, and K, as well as the plant growth, were not affected by the interaction of the N fertilizer form ratio with the types of support. In field conditions, the black pepper prefers the N fertilizer in the form of 50% NO3-:50% NH4+. The pepper plants that were given N fertilizer in a combination of 50% NO3-:50% NH4+ have demonstrated an N, P, and K uptake, and morphology and plant dry weight were higher than the ratio of other forms of N fertilizers.